2010
DOI: 10.2105/ajph.2009.187930
|View full text |Cite
|
Sign up to set email alerts
|

Global Inequality in Eye Health: Country-Level Analysis From the Global Burden of Disease Study

Abstract: Creating new eye health service for refractive errors and reducing the unacceptable eye health disparity in refractive errors should be the highest priorities for international public health services in eye care and eye health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
94
2
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(102 citation statements)
references
References 17 publications
4
94
2
2
Order By: Relevance
“…A previous study demonstrated that cataract ranked as the most unevenly distributed eye disorder in 2004, with higher DALYs in low-and middle-income countries. 17 The World Health Survey in 70 countries showed that the prevalence of vision difficulty in low-income countries was two times higher than that in high-income countries. 18 Among the 21 Super Regions, the prevalence of cataract blindness was highest in Oceania, followed by South and Southeast Asia, and the lowest in high-income countries.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that cataract ranked as the most unevenly distributed eye disorder in 2004, with higher DALYs in low-and middle-income countries. 17 The World Health Survey in 70 countries showed that the prevalence of vision difficulty in low-income countries was two times higher than that in high-income countries. 18 Among the 21 Super Regions, the prevalence of cataract blindness was highest in Oceania, followed by South and Southeast Asia, and the lowest in high-income countries.…”
Section: Discussionmentioning
confidence: 99%
“…Spearman's Rank correlation public awareness strategies for ocular disease [3]. Furthermore, the lack of equipment and other resources requires the centralisation of those services that are available, which renders eye health interventions inaccessible to the majority [15]. The combined effects of such contextual barriers to equitable eye health services include a failure to detect and treat glaucomatous disease for the vast majority of cases (likely very close to 100%, compared to the estimated 50% undiagnosed rate in developed countries), and high prevalence of unilateral and bilateral blindness at the time of presentation and disease detection [16,17].…”
Section: The Moorfields Motion Displacement Testmentioning
confidence: 99%
“…2 Since refractive error manifests at a young age, the number of associated blind-person-years from URE was double the estimate for individuals blind from cataract. 3 URE is the single largest contributor to the global burden of eye diseases 4 and among children it is the leading and most easily remedied cause of poor vision. 5 The prevalence of refractive error among school students in Nigeria varies between 1.97% and 5.8%.…”
Section: Introductionmentioning
confidence: 99%
“…Other factors responsible include nonavailability or inability to afford refractive services, insufficient provision of affordable corrective lenses and cultural disincentives to compliance. 10 About 90% of the burden of eye disease occurs in lowand middle-income countries 4 where access to refraction services and the availability of spectacles are generally poor. 11 One approach to make refractive services readily available and affordable is the introduction of a simple device called a 'focometer'.…”
Section: Introductionmentioning
confidence: 99%